Cross-learning between project management and international development: Analysis and research agenda. Issue 8 (November 2020) - Ika, Lavagnon A.; Söderlund, Jonas; Munro, Lauchlan T.; Landoni, Paolo
Abstract: Both project management and international development came of age as scholarly and practice domains in the 20th century. They share a central concern with organizing work and delivering change. Though international development played a role in defining the project management domain in the 1950s and the 1960s, there has been little cross-fertilization between project management and international development in recent decades. The centrality of projects in international development efforts and the need for project management to help tackle global challenges that overlap with international development, such as climate change and COVID-19, make such cross-learning timely and rewarding. Accordingly, with the aim of cross-fertilization and integration, this paper examines what connects and differentiates the two domains of project management and international development, both conceptually and through the distinctive nature of their modes of delivery. The paper lays out a research agenda for the interface between project management and international development.